Safety, tolerability, and immunogenicity of V114, a 15-valent pneumococcal conjugate vaccine, administered concomitantly with influenza vaccine in healthy adults aged ≥50 years: a randomized phase 3 trial (PNEU-FLU) - Randall Severance; Howard Schwartz; Ron Dagan; Laurie Connor; Jianing Li; Alison Pedley; Jonathan Hartzel; Tina M. Sterling; Katrina M. Nolan; Gretchen M. Tamms; Luwy K. Musey; Ulrike K. Buchwald; et al. (Taylor & Francis Group, 2022)
Streptococcus pneumoniae and influenza viruses are associated with significant morbidity and mortality in older adults. Concomitant vaccination against these agents reduces hospitalization and mortality rates. This phase 3 trial evaluated safety, tolerability, and immunogenicity of concomitant and non-concomitant administration of V114, a 15-valent pneumococcal conjugate vaccine containing serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19F, 19A, 22F, 23F, 33F, and quadrivalent inactivated influenza vaccine (QIV), in healthy adults aged ≥50 years. Participants (N = 1,200) were randomized 1:1 to receive either V114 administered concomitantly with QIV (concomitant group) or QIV plus placebo (non-concomitant group) on Day 1, followed by placebo (concomitant group) or V114 (non-concomitant group) 30 days later. Randomization was stratified by age and history of pneumococcal polysaccharide vaccine receipt. Overall, 426 (71.0%) and 438 (73.5%) participants in the concomitant and non-concomitant groups experienced solicited injection-site adverse events (AEs); 278 (46.3%) and 300 (50.3%) reported solicited systemic AEs. Most solicited AEs were mild or moderate in severity and of short duration. Non-inferiority for pneumococcal- and influenza-specific antibody responses (lower bound 95% confidence interval of opsonophagocytic activity [OPA] and hemagglutination inhibition geometric mean titers [GMTs] ratios ≥0.5) was demonstrated for concomitant versus non-concomitant administration for all 15 pneumococcal serotypes and all four influenza strains. Consistent with previous studies, a trend was observed toward lower pneumococcal OPA GMTs in the concomitant versus the non-concomitant group. V114 administered concomitantly with QIV is generally well tolerated and immunologically non-inferior to non-concomitant administration, supporting coadministration of both vaccines.